Effects of Heat Treatment on the Corrosion Behavior of ASTM A-36 Steel - Alenezi, I. (Engineering, Technology & Applied Science Research, 2020)
The effects of different tempering temperatures and heat treatment times on the corrosion resistance of rolled ASTM A-36 steel in various concentrations of hydrochloric acid (HCl) and sodium chloride (NaCl) were studied in this work, using the conventional weight loss measurement. Rolled and heat-treated specimens were placed in the acidic media for five days and for seven days in NaCl, respectively, and the corrosion rates were evaluated. The microstructure of steel before and after heat treatment was studied. Corrosion resistance revealed remarkable changes from the effect of tempering after water or oil quenching of steel. Generally, the corrosion rate increases from the effect of steel hardening. Tempering of water-quenched steel at 450Co for one hour highly improves the corrosion resistance of 0.27% carbon steel.